British and Iran: Harmful harvest of 1951 oil negotiations - Ebrahimi, Mansoureh (Canadian Center of Science and Education, 2015)
When Dr. Mohammad Mosaddeq began nationalizing the oil industry in 1951, the British were taken aback by his recalcitrant position and did everything possible to maintain their absolute dominance of the industry. Three rounds of negotiations were held but all failed to reach a settlement. This study describes a series of oil agreements between Iran and Britain and further delineates Dr. Mosaddeq’s policies, strategies and counter-proposals with respect to bi-literal political-economic interests. A qualitative approach is employed to disclose the unscrupulous methods employed by the British to maintain their interests in Iran both before and after Iran's nationalization of the oil industry. We used documentation from the Public Records Office, Kew London (cited with 'G' or 'EP'), which bear significant evidence that substantiates the purpose of this study which reveals that all oil agreements, as imposed by the British, were unilateral in nature. Dr. Mosaddeq made a very courageous move when he unilaterally broke from unreasonable contracts that were solely designed to protect the British 'status-quo'. Their actions resulted in negative impacts and responses on/to the ongoing negotiations: “Owing to Persian nationalist susceptibilities there is not the slightest hope of success in a direct negotiation Government vis-à-vis Government”—letter from George Binney to Lord Leathers; The Persian Situation, Argument for the Project. 9 Jan. 1952—whereby two months before the British embassy, in its report dated on 19 November 1951, insisted that “any government is better than Dr. Mosaddeq’s government” (British Embassy, Tehran, G10101/453/51, 19 Nov. 1951).